Numerical Investigation of Motive Pressure on Condensation and Evaporation Process in Steam Ejector of Renewable Refrigeration System - Rakibul Islam; Amir Sohel; Md Faisal Bin Ashab (Advances in Engineering and Intelligence Systems)
In today's life, it is very necessary to use cooling systems in the domestic and industrial cooling process, and the air-conditioning and refrigeration industry has the highest rate of electrical energy consumption in countries with hot weather. Therefore, it is very important to find a cycle with low energy consumption. Ejector refrigeration cycle can be a suitable option due to low energy consumption and compatibility with the environment. This study investigates the effect of pressure of motive flow on refrigeration cycle’s ejector performance. The k-wSST turbulence model and the non-equilibrium condensation model are used to simulate the ejector. According to the results, the present model can well predict the flow behavior in the ejector. As the pressure of motive flow increases, the minimum pressure and minimum temperature in the ejector decreases and the maximum Mach number increases in the ejector, and the production entropy and COP decrease. The pressure of motive flow has a significant effect on the oblique shocks and shock train. The entrainment ratio, which is one of the most important parameters of the ejector, decreases with increasing pressure of motive flow. As the pressure increases from 1.98 bar to 4.75 bar, the entrainment ratio decreases by 62%, the primary flow rate increases from 0.000693 kg/s to 0.001597 kg/s, and a 130% increase in the primary flow rate is seen.